Towards a glottometric analysis of the vocabulary of the Historical Palaea - Илиева, Татяна (Studia Ceranea, 2015)
The present study is an attempt to apply statistical methods in investigating the vocabulary of Old Bulgarian on the basis of lexical material from the Historical Palaea. Tables and charts are used to present a glotometric characterization of the lexical material under study. A comparison is made with data from other Old Bulgarian written monuments that have already been the object of similar studies.